2014
DOI: 10.1177/0096340214531178
|View full text |Cite
|
Sign up to set email alerts
|

Breeder reactors: A possible connection between metal corrosion and sodium leaks

Abstract: Many countries have long pursued fast neutron breeder reactors, which create more fissile fuel than they consume, because of the expectation that the world will run out of the low-cost uranium used for fuel in most commercial nuclear power reactors. Despite billions of dollars spent on research and development, however, fast neutron reactors have proven unreliable and are frequently shut down due to leaks of their sodium coolant. Different reactors around the world have experienced this leakage problem, indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Liquid-metal-cooled fast reactors in France, Russia, the United States, Germany, the United Kingdom, Japan, India, and China have all suffered leaks or accidents, and many are no longer in operation (Pillai & Ramana 2015). Chemical interactions between carbon in stainless steel reactor components and the liquid sodium used as coolant may be a source of corrosion and leaks (Pillai & Ramana 2015); other problems associated with fast reactors include embrittlement, swelling of fuel cladding, and fission gas release (Walters et al 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid-metal-cooled fast reactors in France, Russia, the United States, Germany, the United Kingdom, Japan, India, and China have all suffered leaks or accidents, and many are no longer in operation (Pillai & Ramana 2015). Chemical interactions between carbon in stainless steel reactor components and the liquid sodium used as coolant may be a source of corrosion and leaks (Pillai & Ramana 2015); other problems associated with fast reactors include embrittlement, swelling of fuel cladding, and fission gas release (Walters et al 2011).…”
mentioning
confidence: 99%
“…Chemical interactions between carbon in stainless steel reactor components and the liquid sodium used as coolant may be a source of corrosion and leaks (Pillai & Ramana 2015); other problems associated with fast reactors include embrittlement, swelling of fuel cladding, and fission gas release (Walters et al 2011).…”
mentioning
confidence: 99%
“…"If you have a bunch of Traveling Wave Reactors out there, you really don't have to build any more enrichment plants," said Kevan Weaver, director of technology integration at TerraPower. 5 Expert reviews, though, have also found technical problems with fast reactors, in particular sodium leaks, which, while not deadly, have made past reactors prone to shutdowns, which increases the cost of electricity produced (Pillai and Ramana 2014). And though liquid sodium has some safety advantages as a coolant, it also reacts violently with water and burns if exposed to air; liquid-sodium-cooled fast reactors have been shut down for long periods by sodium fires (Cochran et al 2010).…”
mentioning
confidence: 99%